Analysis of the Implementation of Total Quality Management (TQM) in Improving Employee Performance at PT Permata Bank Cibubur Branch - Rizkia, Nanda Dwi; Mamat Hidayat; Yusi Roslina Suciati; Redi Setiyadi; Putie Nadya Pratiwi; Mira Veranita (PT FORMOSA CENDEKIA GLOBAL, 2024)
A company is an organization operated by the people within it to achieve the company's objectives. To achieve product quality, the implementation of an efficient management system is necessary, serving as both a tool for improving company performance and a measure of employee performance. The company's focus is not only limited to the quality of the products produced but also covers aspects such as processes, human resources, and the environment. Therefore, it is important to include the measurement of productive behavior of employees and to be based on quality improvement, which is also grounded in human resource development. This research is qualitative in nature. Data was collected through observation, interviews, and documentation. The theory applied in this research is the Quality Management Theory. The research results indicate that the company's performance in providing quality products and services in the era of globalization is continuously increasing, both in terms of human skills, processes, and the environment. This comprehensive improvement is achieved through the Total Quality Management (TQM) approach. Through efficiently managed TQM, parts of the company that require improvements or changes can be identified